Karya Karawitan Inovatif “Ngincung” - I Made Agus Natih Sutyasa; Saptono Saptono; I Ketut Muryana (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2023)
Pangilen can be interpreted as a procession carried out through certain stages or steps tailored to the type of ritual activity. There are several series of pangilen processions, one of which is the Ngincung procession. The term ngincung is the last procession or the closing part in the stages of the Pangilen-ilen Mangku procession in Kesiman village. This work is realized in the form of an innovative musical work using the medium of expression of Semar Pegulingan and Selonding gamelan. This innovative musical work is divided into 3 parts with a duration of 12 minutes, using 17 musicians, including the composer. The creation method used in creating this innovative musical work entitled Ngincung is the Alma M. Hawkins creation method, which contains three stages: the exploration stage, the experimental stage, and the formation stage. Research, observation, or interviews are conducted in the exploration stage on the idea raised. After getting the idea raised for the Innovative Karawitan work, move on to the second stage, which is experimentation. In the experimental stage, the idea was put into the form of a musical piece. After that, we began the formation stage by starting the process of rehearsing the work with the supporters of the work, starting with determining a good day to do nuasen.